The end of men : and the rise of women - Hanna Rosin (Riverhead Books, 2012)
Men have been the dominant sex since the dawn of mankind. But the author has noticed that this long-held truth is, astonishingly, no longer true. At this unprecedented moment, by almost every measure, women are no longer gaining on men: they have pulled decisively ahead. And "the end of men", the title of her Atlantic magazine cover story on the subject, has entered the lexicon as dramatically as Betty Friedan's "Feminine Mystique," Simone de Beauvoir's "Second Sex," Susan Faludi's "Backlash," and Naomi Wolf's "Beauty Myth" once did. In this book, the author reveals how this new state of affairs is radically shifting the power dynamics between men and women at every level of society, with profound implications for marriage, sex, children, work, and more. With wide-ranging curiosity and insight unhampered by assumptions or ideology, the author shows how the radically different ways men and women today earn, learn, spend, couple up, even kill, has turned the big picture upside down.